Integrated approach to customer requirement using quality function deployment and Kansei engineering to improve packaging design - Mohamad, Effendi; Faishal, Muhammad; Adiyanto, Okka; Jaafar, Roshidah; Abdul Rahman, Azrul Azwan; Jatmiko, Hapsoro Agung; Novera, Ijmal (Research and Technology Transfer Affairs Division, Khon Kaen University, 2021)
Packaging is one of the attributes that has a significant impact on the sale of a product. Specifically, it helps customers to notice the product, and it influences their decision to purchase. Several SMEs in Yogyakarta, including those producing crispy wader fish, have failed when it comes to the packaging of their products. This product does not appeal to customers because it is wrapped in transparent plastic. The purpose of this study was to recommend a packaging design for the crispy wader fish product that would attract customers. The first step in this study was to conduct a survey to obtain the Kansei words that could be split into nine categories, including material, model, price, durability, informative, safety, size, appearance, and easy to care. Furthermore, the quality function deployment (QFD) method was used to evaluate the desires of customers in order to design an eye-catching packaging that would meet their expectations. A total of 23 Kansei words were collected, based on an analysis of surveys and interviews. These words were interpreted using QFD to generate eight characteristics, namely, availability, cleanliness, display, durability, power, price, protection, and standard size. These characteristics were used to help develop an appealing outer packaging design. Photoshop software was used to develop the 3D model, while design methods were aligned with the achievement targets of the House of Quality (HoQ), which required the outer packaging to be appealing and disposable to fulfil consumer expectations.